Magnetization transfer ratio measures in normal-appearing white matter show periventricular gradient abnormalities in multiple sclerosis - Liu, Zheng; Pardini, Matteo; Yaldizli, Özgür; Sethi, Varun; Muhlert, Nils; Wheeler-Kingshott, Claudia A. M.; Samson, Rebecca S.; Miller, David H.; Chard, Declan T. (Brain (London, England : 1878), 2015)
In multiple sclerosis, there is increasing evidence that demyelination, and neuronal damage occurs preferentially in cortical grey matter next to the outer surface of the brain. It has been suggested that this may be due to the effects of pathology outside the brain parenchyma, in particular meningeal inflammation or through cerebrospinal fluid mediated factors. White matter lesions are often located adjacent to the ventricles of the brain, suggesting the possibility of a similar outside-in pathogenesis, but an investigation of the relationship of periventricular normal-appearing white matter abnormalities with distance from the ventricles has not previously been undertaken. The present study investigates this relationship in vivo using quantitative magnetic resonance imaging and compares the abnormalities between secondary progressive and relapsing remitting multiple sclerosis. Forty-three patients with relapsing remitting and 28 with secondary progressive multiple sclerosis, and 38 healthy control subjects were included in this study. T1-weighted volumetric, magnetization transfer and proton density/T2-weighted scans were acquired for all subjects. From the magnetization transfer data, magnetization transfer ratio maps were prepared. White matter tissue masks were derived from SPM8 segmentations of the T1-weighted images. Normal-appearing white matter masks were generated by subtracting white matter lesions identified on the proton density/T2 scan, and a two-voxel perilesional ring, from the SPM8 derived white matter masks. White matter was divided in concentric bands, each ∼1-mm thick, radiating from the ventricles toward the cortex. The first periventricular band was excluded from analysis to mitigate partial volume effects, and normal-appearing white matter and lesion magnetization transfer ratio values were then computed for the 10 bands nearest to the ventricles. Compared with controls, magnetization transfer ratio in the normal-appearing white matter bands was significantly lower in patients with multiple sclerosis. In controls, magnetization transfer ratio was highest in the band adjacent to the ventricles and declined with increasing distance from the ventricles. In the multiple sclerosis groups, relative to controls, reductions in magnetization transfer ratio were greater in the secondary progressive multiple sclerosis compared with relapsing remitting multiple sclerosis group, and these reductions were greatest next to the ventricles and became smaller with distance from them. White matter lesion magnetization transfer ratio reductions were also more apparent adjacent to the ventricle and decreased with distance from the ventricles in both the relapsing remitting and secondary progressive multiple sclerosis groups. These findings suggest that in people with multiple sclerosis, and more so in secondary progressive than relapsing remitting multiple sclerosis, tissue structural abnormalities in normal-appearing white matter and white matter lesions are greatest near the ventricles. This would be consistent with a cerebrospinal fluid or ependymal mediated pathogenesis.